Net Water Uptake Calculated in Standardized and Blindly Outlined Regions of the Middle Cerebral Artery Territory Predicts the Development of Malignant Edema in Patients With Acute Large Hemispheric Infarction - Xu, Hai-Bin; Sun, Yu-Fei; Luo, Na; Wang, Jia-Qi; Chang, Guo-Can; Tao, Lin; Yang, Ben-Qiang; Chen, Hui-Sheng (Frontiers in Neurology, 2021)
Background and purpose: Previous studies have demonstrated that Net Water Uptake (NWU) is associated with the development of malignant edema (ME). The current study aimed to investigate whether NWU calculated in standardized and blindly outlined regions of the middle cerebral artery can predict the development of ME. Methods: We retrospectively included 119 patients suffering from large hemispheric infarction within onset of 24 hours. The region of the middle cerebral artery territory was blindly outlined in a standard manner to calculate NWU. Patients were divided into two groups according to the occurrence of ME, which is defined as space-occupying infarct requiring decompressive craniotomy or death due to cerebral hernia in 7 days from onset. The clinical characteristics were analyzed, and receiver operating characteristic curve (ROC curve) was used to assess the predictive ability of NWU and other factors for ME. Results: Multivariable analysis showed that NWU was an independent predictor of ME (OR 1.168，95%CI 1.041-1.310) . According to the ROC curve, NWU≥8.127% identified ME with a good predictive power (AUC 0.734, sensitivity 0.656, specificity 0.862). Conclusions: NWU calculated in standardized and blindly outlined regions of the middle cerebral artery territory is also a good predictor for the development of ME in patients with large hemispheric infarction.